IMPLEMENTASI PENDEKATAN SOCIO SCIENTIFIC ISSUES PADA MATERI ENERGI TERBARUKAN UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF SISWA KELAS X SMA - Rahayu Sihombing, Selvy; Z, Fakhruddin; Nasir, Muhammad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of teaching using the Socio Scientific Issues (SSI) approach on students’ cognitive learning outcomes in the field of renewable energy. The research method employed was quantitative, using a quasi-experimental design in the form of a control group with a post-test only. The research sample consisted of two classes: an experimental class that received SSI based instruction and a control class that received conventional instruction. The instrument used was a post-test. The data were analysed using normality tests, homogeneity tests, and independent samples t-tests. The results indicated a significant difference between the cognitive learning outcomes of students in the experimental class and the control class, with a significance level of <0.05. Thus, teaching using the Socio Scientific Issues approach has an effect on improving students’ cognitive learning outcomes in the field of renewable energy.